Students' Critical Thinking Ability Reviewed Learning Styles in Learning with SCAMPER Method the Assisted by E-Module - Sarifuddin, Muhamad; Isnarto, Isnarto; Wiyanto, Wiyanto (Universitas Negeri Semarang, 2021)
The ability to think critically is a must for students in the learning process because it can support understanding a problem appropriately and systematically. This research aims to describe the quality of learning with SCAMPER method the assisted by e-module on students’ critical thinking ability and describe students’ critical thinking ability in terms of learning styles. This type of research is mixed method research. The subjects in this study were students of class XI AKL 2 in the academic year 2020/2021. Data obtained from critical thinking ability tests, learning style questionnaires, student response questionnaires, and interviews. The quantitative data analysis includes the average achievement test, the proportion test, the average difference test, the proportion difference test, and the average increase difference test. Qualitative data analysis includes data reduction, data presentation, and making conclusions. The results showed that learning mathematics using the SCAMPER method assisted by e-module can be said to be of high quality. This is based on the results at the planning stage and the implementation stage in the minimal good category and at the assessment stage, it is said to be effective. Students’ critical thinking ability viewed from the learning style in learning with the SCAMPER method assisted by e-module that to get the high category TKBK at least master three indicators, the medium category students master two indicators, and the low category master at most one indicator.